Narrating Global Order and Disorder - Levinger, Matthew (2017)
This thematic issue addresses how strategic narratives affect international order. Strategic narratives are conceived of as stories with a political purpose or narratives used by political actors to affect the behavior of others. The articles in this issue address two significant areas important to the study of international relations: how strategic narratives support or undermine alliances, and how they affect norm formation and contestation. Within a post-Cold War world and in the midst of a changing media environment, strategic narratives affect how the world and its complex issues are understood. This special issue speaks to the difficulties associated with creating creative and committed international cooperation by noting how strategic narratives are working to shape the Post-Cold War international context.